A photoexcited halogen-bonded EDA complex of the thiophenolate anion with iodobenzene for C(sp3)–H activation and thiolation. Issue 47 (28th October 2021) - Li, Tao; Liang, Kangjiang; Tang, Jiaying; Ding, Yuzhen; Tong, Xiaogang; Xia, Chengfeng
Abstract : A direct photochemical thiolation of C(sp 3 )–H bond-containing substrates with thiophenol was developed. A halogen bonding-type EDA complex was found to trigger the downstream single electron transfer and hydrogen atom transfer process. Abstract : Thiophenol was discovered to form an EDA complex with iodobenzene through halogen bonding interactions upon treatment with KOH. A direct photochemical thiolation of C(sp 3 )–H bond-containing etheric, allylic, and benzylic substrates with thiophenol was developed. The reaction proceeded on the basis of the in situ generation of a thiyl radical and aryl radical through single electron transfer between the photoexcited thiophenolate anion and aryl iodide EDA complex. Then a C(sp 3 ) centred-radical was formed by aryl radical-mediated hydrogen atom transfer and the thiolation products were delivered via a radical–radical cross-coupling with the thiyl radical.